Ultrasound detected inflammation is associated with the development of new bone erosions in hand osteoarthritis: a longitudinal study over 3.9 years. Issue 11 (November 2015) - Mancarella, L.; Addimanda, O.; Pelotti, P.; Pignotti, E.; Pulsatelli, L.; Meliconi, R.
Summary: Objective: To evaluate the association between ultrasound (US) detected inflammation at baseline and the subsequent development of new bone erosions at follow-up in patients with hand osteoarthritis (HOA). Method: 32 of the 35 (10 controls, 12 patients with non erosive HOA (non-EHOA), 13 with EHOA subjects originally studied were re-evaluated 3.9 years after the initial study, by means of standard radiography and US examination. Kellgren–Lawrence (K-L) and Kallman scores were utilized to evaluate 576 interphalangeal (IP) joints. US detected synovial inflammation features were scored as present/absent. US detected bone erosions were also investigated. The association between synovial inflammation features at baseline and the development of new bone erosions was evaluated using the generalized linear mixed model (GLMM) after adjustment for patient effect, age, gender, body mass index. Results: In HOA patients, radiographic scores worsened and bone erosions progressed. In HOA patients similar percentages of joints with Power Doppler Signal (PDS) and gray scale (GS) synovitis were found comparing baseline and follow-up examinations, whilst a significant increase was found in the joints with effusions. Only a minority of joints were positive on both occasions (between 2 and 6 %), the majority fluctuated between positive and negative and vice versa. PDS positivity was associated with new radiographic central erosions and US-detected bone erosions, whereas GS synovitis and effusion were not. Conclusions: Radiographic scores and bone erosions increased over a period of about 4 years. Synovial inflammation as detected by PDS was associated with the appearance of new bone erosions.